Analyzing Thematic Structure of Text Drama Swan Song in English and Indonesian Version: A Descriptive Analysis - Yasir Riady; Ahmad Jum’a Khatib Nur Ali (Pusat Studi Bahasa dan Publikasi Ilmiah, 2019)
Language is a very effective tool in communication. By using language people are able to express their thought, experiences, ideas, opinions, and hopes to each other. Discussing about language, one of the sub-parts of language is translation. Swan song is one of Chekov’s famous plays. There are so many performances in Indonesia who used the translation’s version of Swan song that translated into Nyanyian Angsa and many directors try to adapt the story, it is interesting to find out the thematic structures in both versions, that is why the writers try to explore the structures both in two versions.